Fifteenth ACM Conference on Recommender Systems 2021
DOI: 10.1145/3460231.3478843
|View full text |Cite
|
Sign up to set email alerts
|

Analyzing Item Popularity Bias of Music Recommender Systems: Are Different Genders Equally Affected?

Abstract: Several studies have identified discrepancies between the popularity of items in user profiles and the corresponding recommendation lists. Such behavior, which concerns a variety of recommendation algorithms, is referred to as popularity bias. Existing work predominantly adopts simple statistical measures, such as the difference of mean or median popularity, to quantify popularity bias.Moreover, it does so irrespective of user characteristics other than the inclination to popular content. In this work, in cont… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(9 citation statements)
references
References 15 publications
0
9
0
Order By: Relevance
“…Zooming in on another user characteristic, several studies investigate gender. They show that popularity bias particularly affects minority gender groups (in these studies: women), resulting in lower-quality recommendations in terms of accuracy and coverage (e.g., Lesota et al, 2021;Melchiorre et al, 2021). In addition to finding similar results for user gender, Ekstrand et al (2018) and its reproducibility study by Neophytou et al (2022) found performance differences for different user age groups, too.…”
Section: User Perspectivementioning
confidence: 73%
“…Zooming in on another user characteristic, several studies investigate gender. They show that popularity bias particularly affects minority gender groups (in these studies: women), resulting in lower-quality recommendations in terms of accuracy and coverage (e.g., Lesota et al, 2021;Melchiorre et al, 2021). In addition to finding similar results for user gender, Ekstrand et al (2018) and its reproducibility study by Neophytou et al (2022) found performance differences for different user age groups, too.…”
Section: User Perspectivementioning
confidence: 73%
“…Parallel to the former study, these studies also found that the users' interests in popular items highly differ, and individuals interested in long‐tail items receive more unfair recommendations than others for both domains. Also, another related study 17 has analyzed the discrepancies between the popularity of items in the profiles of users and the produced recommendation lists for users of different genders and concluded that females are more affected by such algorithmic popularity bias in music recommendations compared to males. Besides, another recent research 15 has considered various discriminative attributes related to rating behaviors of users, such as profile size, profile mean, profile deviation, profile anomaly, and profile entropy, and analyzed their potential relations with the unfairness propagation of the recommender systems.…”
Section: Related Workmentioning
confidence: 99%
“…A few recent studies have reperformed such analyses for users in protected classes, such as age 16 or gender. 17 However, keeping in mind that personality traits are critical elements for understanding the behavior of individuals, to the best of our knowledge, how users' popularity inclination in their original profiles varies concerning their personality characteristics has not yet been examined in the literature. More importantly, how popularity bias affects individuals with different characteristics is still elusive.…”
Section: Problem Statement and Motivationmentioning
confidence: 99%
See 1 more Smart Citation
“…Their experiment showed that unfairness in location recommender systems is likely related to location popularity or inclination toward some user groups based on nationality. Lesota et al [21] investigated item popularity fairness in the music domain using the LFM-2b 6 dataset, i.e., P-fairness, and addressed shortcomings of the statistical analysis in fairness by considering the distribution between user-profiles and recommendation lists. Furthermore, they analyzed whether such algorithmic popularity bias affects users of different genders.…”
Section: Related Workmentioning
confidence: 99%